Manganese doped-iron oxide nanoparticles and their potential as tracer agents for magnetic particle imaging (MPI) - Dogan, N.; Dogan, O. M.; Irfan, M.; Ozel, F.; Kamzin, A. S.; Semenov, V. G.; Buryanenko, I. V. (ELSEVIER, 2022)
Manganese doped iron oxide nanoparticles based on the chemical formula MnxFe3-xO4 (where x = 0.00, 0.50, and 1.00) have been prepared with different concentrations of manganese-oleate, and iron-oleate by thermal treatment method. To prevent nanoparticle from agglomeration and increase surface functioning, oleate was employed as a capping agent to create stable nanoparticles for magnetic particle imaging (MPI). Mn-doped magnetite nanoparticles (MnxFe3-xO4) were synthesized by the thermal decomposition method. Manganesebased iron oxides were morphologically assessed by x-ray diffraction (XRD), fourier transformed infrared spectroscopy (FTIR), and thermogravimetric analysis (TGA). Manganese-based iron oxides were also magnetically examined with electron-spin resonance (ESR), physical properties measurement system (PPMS), and magnetic particle relaxometer (MPR). Additionally, phase composition and iron concentration of the manganesebased nanoparticles were determined with the Mossbauer spectra (MS) technique. The crystallite size of 11-18 nm was achieved with the XRD technique for MnxFe3-xO4. MnFe2O4 (x = 1.00) revealed high stability at higher temperatures according to TGA analysis and high saturation magnetization at room temperature as compared to other manganese concentrations. MPR demonstrated the shortest relaxation time of MnFe2O4 as compared to commercially MPI tracer agents such as Vivotrax (magnetic insight) and Perimag (micromod). The finding of this study emphasizes that manganese ferrites have the immense potential to become the optimum tracer agent for MPI applications.
Keywords: Magnetic particle imaging; Manganese ferrites; Thermal decomposition; Magnetic particle spectroscopy; Mossbauer spectra; Superparamagnetic iron oxides; ELECTRON-SPIN-RESONANCE; FERRITE NANOPARTICLES; FE3O4 NANOPARTICLES; TEMPERATURE; MOSSBAUER; ABSORPTION; MNFE2O4; SHELL; MN; Materials Science; Physics